Expression of modulators of extracellular matrix structure after anterior cruciate ligament injury. Issue 1 (January 2014) - Haslauer, Carla M.; Proffen, Benedikt L.; Johnson, Victor M.; Murray, Martha M.
Abstract The ability of the anterior cruciate ligament (ACL) to heal after injury declines within the first 2 weeks after ACL rupture. To begin to explore the mechanism behind this finding, we quantified the expression of genes for collagen I and III, decorin, tenascin‐C, and alpha smooth muscle actin, as well as matrix metalloproteinase (MMP)‐1 and ‐13 gene expression within multiple tissues of the knee joint after ACL injury in a large animal model over a 2‐week postinjury period. Gene expression of collagen I and III, decorin, and MMP‐1 was highest in the synovium, whereas the highest MMP‐13 gene expression levels were found in the ACL. The gene expression for collagen and decorin increased over the 2 weeks to levels approaching that in the ligament and synovium; however, no significant increase in either of the MMPs was found in the provisional scaffold. This suggests that although the ACL and synovium up‐regulate both anabolic and catabolic factors, the provisional scaffold is primarily anabolic in function. The relative lack of provisional scaffold formation within the joint environment may thus be one of the key reasons for ACL degradation after injury.